Історичні та сучасні аспекти методів ангіовізуалізації ішемічної хвороби серця (огляд літератури) - Губка, Віктор Олександрович; Вайло, Юрій Миколайович; Матерухін, Аркадій Миколайович; Макаренков, А. Л.; Hubka, V. O.; Vailo, Yu. M.; Materukhin, A. M.; Makarenkov, A. L. (Запорізький державний медико-фармацевтичний університет, 2023)
Мета роботи – узагальнити та розширити знання про сучасні методи, що застосовують для візуалізації вінцевих артерій, їхню еволюцію, можливості, ефективність, показання до використання, безпечність для пацієнта, які ґрунтуються на принципах доказової медицини. Встановити етіологічну причину ішемії міокарда можна лише після візуалізації ВА. Лікар-практик має змогу візуалізувати ВА за допомогою рентгенконтрастної коронароангіографії або комп’ютерної томографії органів грудної клітки з контрастним підсиленням. Методи візуалізації ВА застосовують у клінічній практиці вже понад пів сторіччя. Постійно оновлюють апаратну частину та програмне забезпечення, удосконалюють і розширюють діагностичні можливості цих методів, оновлюють рекомендації щодо їх застосування у загальноклінічній практиці. Головне завдання для клініциста – підтвердити чи спростувати наявність атеросклеротичного ураження ВА, а також встановити його локалізацію, поширення, ступінь стенозування, значущість для коронарного кровотоку, наявність кальцинозу ВА, колатеральних шляхів, склад бляшки та її внутрішню структуру. Лише після визначення усіх анатомічних і фізіологічних аспектів атеросклеротичного процесу в ВА можна обрати правильну стратегію лікування пацієнта мультидисциплінарною серцевою командою: фармакологічну терапію, метод реваскуляризації серця та заходи щодо первинної чи вторинної профілактики.

The aim of the work. To summarize and expand knowledge about current methods used for visualization of coronary arteries, their evolution, capabilities, effectiveness, indications for use, safety for patients, guided by the principles of evidence-based medicine. Coronary artery disease (CАD) is an extremely common clinical cardiovascular disease, which is caused by atherosclerosis of the subepicardial coronary arteries (CAs) and can have both acute and chronic course. The incidence of CАD is increasing every year and getting younger. CАD has not only a high morbidity rate, but also a high mortality rate. In Ukraine, mortality from CАD isthe main cause of population mortality. Without timely diagnosis and effective treatment, myocardial infarction or sudden cardiacdeath may develop. It is possible to ascertain the etiological cause of myocardial ischemia only after visualization of the СAs. A practicing physician is able to visualize the СAs using X-ray contrast coronary angiography or contrast-enhanced computed tomography of the chest. СA visualization methods have been used in clinical practice for more than half a century. The hardware and software are constantlyupgraded, the diagnostic options of these methods are improved and expanded, and recommendations regarding their use ingeneral clinical practice are updated. The main task for clinicians is to confirm or rule out the presence of a СA atheroscleroticlesion, as well as to determine its localization, extent, degree of stenosis and its significance for coronary blood flow, the presenceof СA calcification, collateral pathways, plaque composition and its internal structure. Only after identifying the anatomical andphysiological aspects of the atherosclerotic process in СA, it is possible to choose the right strategy for the treatment of patientsby a multidisciplinary heart team including pharmacological therapy, a method of cardiac revascularization, and measures forprimary or secondary prevention.
Historical and current aspects of angiovisualization methods in CАD (a literature review)
Губка В. О. - ORCID: 0000-0002-6912-8577; Вайло Ю. М. - ORCID: 0000-0003-3132-1352; Матерухін А. М. - ORCID: 0000-0003-2856-6703.
Keywords: ішемічна хвороба серця; візуалізація вінцевих артерій; коронароангіографія; КТ-коронарографія; сoronary artery disease; visualization of coronary artery; coronary angiography; CT coronary angiography